Why do Canadians host refugees? A sequential explanatory mixed-methods study protocol - Areej Al-Hamad; Yasin Yasin; Kateryna Metersky; Aryan Karimi; Sepali Guruge; Maher El-Masri; Riham Al-Saadi (PLoS ONE, 2026)
Refugee homestay hosting, in which private citizens or permanent residents provide temporary accommodation and informal support to refugees and displaced persons, is increasingly used as a community-based response to housing insecurity, social isolation, and settlement barriers. Although prior scholarship has examined refugee experiences within hosting arrangements, comparatively little is known about the motivations, readiness, attitudes, empathy, satisfaction, and advocacy behaviours of hosts, or about the organizational supports required to sustain hosting in Canada. The study is informed by hospitality studies and collective action perspectives. This protocol describes a 36-month sequential explanatory mixed-methods study of three phases designed to examine why Canadians host refugees and how refugee homestay hosting can be strengthened through evidence-informed and co-designed strategies. Phase 1 will include the administration of a national survey to current and former Canadian refugee homestay hosts to examine relationships among hospitableness, attitudes toward refugees, empathy, readiness to assist, satisfaction, and advocacy for refugee hosting. Quantitative data will be analyzed using descriptive and inferential statistics. Open-ended survey responses will be thematically analyzed. Phase 2 will use qualitative descriptive methods to conduct semi-structured interviews with 20–25 Canadian hosts and service providers to explore motivations, practices, needs, challenges, trauma- and gender-responsive considerations, and recommendations for service and policy improvement. Phase 3 will use group concept mapping and co-design sessions with 20–25 hosts and service providers to prioritize needs and develop multi-level action-oriented recommendations, including a host support toolkit, service provider guidelines, and policy strategies. Findings are expected to inform refugee-serving organizations hosting practices and programs to sustain safe, inclusive, and effective refugee homestay hosting in Canada.